FAKTOR-FAKTOR YANG MEMPENGARUHI SISTEM PENGAWASAN PENGELOLAAN KEUANGAN DESA (STUDI KASUS WILAYAH KABUPATEN BOGOR) - Rochman Marota; Asep Alipudin (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
The Village Law gives new meaning related to trust by seeing the village as an institution that is equal to the regional government. The village not only as an institution providing letters or government accomplices, but an institution that independently and has the task of maintaining the welfare of the small unit in the community. These consequences provide a view of the professionalism of performance that can be monitored transparently and accountably. The urgency of this research lies in its objectives and benefits for the government and village officials, namely to provide a complete and factual picture of village supervision and finance from planning, management and accountability as well as strengthening the capabilities of village officials in managing funds and overseeing programs funded by village funds in a way and village development in general. This study concludes that there is a relationship between the stages of village financial management from the process of planning, implementing, administering and reporting to its monitoring system. The good village financial management process showed that the monitoring system was running well.